A new species of Eutyphoeus Michaelsen, 1900 (Clitellata: Acanthodrilidae) from the Eastern Himalaya, India - Kumar, Avnish; Kumar, Anupam; Tiwari, Nalini; Upadhyaya, Chandrama P; James, Samuel W; Yadav, Shweta (Zootaxa, 2026)
A new acanthodrilid earthworm, Eutyphoeus takchangensis sp. nov. is described based on specimens collected from the biodiversity hotspot region of the North-eastern India, in the state of Sikkim, characterized by predominantly chemical-free agriculture practices. Eutyphoeus takchangensis sp. nov. is an avestibulate metandric species that lacks lateral intestinal caecae. The proposed species is distinguished from its congeners by the absence of genital markings and associated glands, the presence of a single female pore and penial setae, and by possessing unidiverticulate spermathecae.